Headache and inflammatory bowel disease: think cerebral vein!. Issue 1 (29th January 2019) - Orfei, Martina; Gasparetto, Marco; Torrente, Franco
Abstract : Cerebral vein thrombosis is a severe complication of inflammatory bowel disease, can cause non-specific symptoms and hence lead to delay in diagnosis. We report the case of an adolescent with inflammatory bowel disease who developed extensive cerebral vein thrombosis requiring a ventriculoperitoneal shunt. Diagnosis was markedly delayed due to repeated misinterpretation of clinical signs and laboratory findings and the lack of reconsidering the working diagnosis despite the involvement of several medical subspecialties. The patient does not suffer from any neurological impairment. This case report highlights the need for clinicians to maintain vigilance for complications of chronic disease and encourages to cast doubt on the working diagnosis constantly.